Implementation of Integrated Islamic Primary School (SRAI) from Administrators’, Teachers’, and Pupils’ Perspectives - Ikhsan Othman; Norila Md. Salleh (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2016)
Integrated Islamic Primary School or in Malaysian Language called Sekolah Rendah Agama Integrasi (SRAI), it a type of primary school in Malaysia which is under the administration of Selangor Islamic Department. SRAI integrates curriculum implemented in Malaysia National Primary School and curriculum implemented in Selangor Islamic Primary School. The two different curriculums are normally implemented in two different sessions and in the two types of the mentioned schools. Upon the operation of SRAI, there are strenghts and weakenesses that can be identified and positively discussed for further enhancement of the schools as this type of schools might someday be proposed or looked as a model school. This paper is based on a study done on the schools. The study focusies on administrators, teachers, and pupils perspectives on the selected issues regarding SRAI. Questionnaires were given to the respondents to seek their perceptions on SRAI. Generally, the findings of the study showed that most aspects in the implementation of SRAI are recieved positively while there are others which need enhancements. Periodic review should be done to monitor the development and situation of the schools from time to time. Sekolah Dasar Islam Terpadu atau dalam bahasa Malaysia disebut Sekolah Rendah Agama Integrasi (SRAI) yaitu salah satu jenis sekolah dasar di Malaysia yang berada di bawah administrasi Departemen Islam Selangor. SRAI mengintegrasikan kurikulum yang diimplementasikan di Sekolah Dasar Negeri Malaysia dan Sekolah Dasar Islam Selangor. Dua kurikulum yang berbeda dilaksanakan secara normal dalam dua sesi yang berbeda dari dua jenis sekolah tersebut. Setelah pelaksanaan SRAI, ada kelebihan dan kelemahan yang dapat diidentifikasi dan baik dibahas untuk peningkatan lebih lanjut dari sekolah sebagai jenis sekolah yang pada kemudian hari akan diusulkan atau diperlihatkan sebagai sekolah model. Makalah ini didasarkan pada kajian yang dilakukan di sekolah-sekolah. Penelitian ini memfokuskan pada perspektif administrator, guru, dan murid tentang isu-isu yang dipilih mengenai SRAI. Kuesioner yang diberikan kepada responden untuk mencari persepsi mereka tentang SRAI. Secara umum, temuan penelitian menunjukkan bahwa sebagian besar aspek dalam pelaksanaan SRAI diterima dengan baik sementara aspek-aspek lainnya membutuhkan peningkatan. Tinjauan secara periodik harus dilakukan untuk memantau perkembangan dan situasi sekolah dari waktu ke waktu.